Should the annual pelvic examination go the way of annual cervical cytology?. (July 2014) - MacLaughlin, Kathy L; Faubion, Stephanie S; Long, Margaret E; Pruthi, Sandhya; Casey, Petra M
The value of pelvic examination for healthy asymptomatic women has been called into question given the lack of benefit for ovarian and endometrial cancer screening, the ability to screen for sexually transmitted infections without a pelvic examination, and the uncoupling of the procurement of contraception with a pelvic examination. Still, there are indications for performing pelvic examinations in symptomatic women and in some high risk women. How do we as clinicians apply current evidence and expert opinion to our medical practice? Our recommendation to consider a pelvic examination at 3−5-year intervals with cervical cancer screening to elicit gynecologic and sexual health concerns offers a compromise between continuation of unnecessary annual pelvic examinations and complete elimination of these examinations.